Optimizing the Early Childhood Education Curriculum by Incorporating Local Wisdom for Holistic Development - Elia (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This research aims to optimize the Early Childhood Education (ECE) curriculum by incorporating local wisdom values to support holistic education. This approach is designed to create an educational program that not only focuses on academic aspects but also on character building, as well as the socio-cultural and emotional development of children. The research method used is qualitative, with a case study approach in several ECE institutions in Pariaman City that have implemented local wisdom values in their curriculum. Data were collected through observation, in-depth interviews, and curriculum document analysis. The results show that the integration of local wisdom values in the ECE curriculum is effective in increasing the sense of community, mutual respect, and cultural understanding among children. In addition, this approach also supports the development of more balanced cognitive and emotional aspects. In conclusion, a local wisdom-based curriculum has great potential to support holistic education in early childhood. For future studies, further research is recommended to examine the effectiveness of this curriculum model in various regions and cultural groups to enrich the variety and increase understanding of the implementation of local wisdom in the context of holistic education in Indonesia